العوامل النفسية والاجتماعية المرتبطة بإقبال النساء على حقن الميزو ثرابي للوجه: دراسة مطبقة على قسم الصيدلة بالمعهد العالي للعلوم والتقنيات الطبية / أبو سليم - هالة غيث بن شتي; أسامة محمد بن رجب (Surman Journal of Science and Technology, 2024)
Plastic surgery is one of the common surgical procedures all over the world, and the popularity of these operations is constantly increasing, including in the Arab world and Libyan society, due to the growing technical and technological medical progress year after year, as these operations have become safer, easier and give accurate results, as medical progress has contributed to the development of many new technologies used in plastic surgery, such as laser, injections and stem cell therapy, and these techniques have led to improved results and increased safety, making Plastic surgeries are more attractive to people, and social media has played a major role in raising awareness of plastic surgery, and clarifying great differences before and after plastic surgery, as celebrities and pioneers of these sites publish their experiences and the results they obtained from these operations, in addition to hospitals and doctors publishing pictures before and after showing the results of these operations, which helped to increase the demand for plastic surgery, and the social and functional factor plays a major role in urging people to undertake plastic surgery, especially when Those who have a large income, the high standard of living and perch income made them. This research dealt with the psychological and social factors associated with women's demand for mesotherapy injections in the face, and the sample consisted of 50 women from the total community sample, represented by some faculty members, employees, teaching assistants and students aged between (30-60) in the field training clinic in the Department of Pharmacy at the Higher Institute of Medical Sciences and Technologies / Abu Salim, and for the small size of the sample, an electronic questionnaire form was used and distributed on social networking sites and consisted of 70 women aged (30 years to 70 year) and the total number of 120 and sorted 70 valid, and used the descriptive approach because it is the most appropriate and the use of a questionnaire form to collect data was designed after referring to some previous studies, and it was found from what the study concluded that the majority of women and those aged (50-60) accept these operations by (80%), and the research showed that the fear of pigmentation and signs of aging was by (56%), and that women are in constant contact with cosmetic clinics through social sites by (42%), and has The research recommended spreading awareness of awareness lectures in universities and women's gathering places such as gymnasiums.